Análise de inflamassoma induzido por urato monossódico em monócitos de gestantes portadoras de pré-eclampsia - Matias, Mariana Letícia [UNESP] (2015)
Preeclampsia (PE) is a specific syndrome of pregnancy, characterized by hypertension and proteinuria, identified after the 20th week of pregnancy. This pathology is associated with hyperuricemia, elevated serum levels of inflammatory cytokines, leukocyte activation and oxidative stress. Uric acid crystals may activate an intracellular complex called inflammasome, a multi-protein structure which is important for processing and release of inflammatory cytokines such as interleukin-1 beta (IL-1β) and IL-18. This study investigated, in pregnant women with PE, the state of monocyte activation both endogenous and stimulated with monosodium urate (MSU), by gene expression of NLRP1 and NLRP3 inflammassomes as well as their association with inflammatory cytokines expression by these cells. Monocytes were obtained from peripheral blood of 23 preeclamptic pregnant women, 23 normotensive pregnant women (NT) in the third trimester of pregnancy and 23 healthy non-pregnant women (NP), and cultured in the presence or absence of 50 μg/mL of MSU for 18 h. Inflammasome activation was evaluated by the gene expression of NLRP1, NLRP3, caspase-1, IL-1β, IL-18 and TNF-α by RT-qPCR in unstimulated monocytes (endogenous expression), or after cell stimulation with MSU (stimulated expression). The concentration of cytokines was assessed by enzyme-linked immunosorbent assay (ELISA). The results were analyzed using non-parametric tests at 5% significance level. In preeclamptic pregnant women, gene expression of NLRP1, NLRP3, caspase-1, IL-1β and TNF-α by monocytes, stimulated or not with MSU, was significantly higher than in NT and NP groups. In addition, there was a higher endogenous expression of IL-18 in pregnant women with PE compared with NT pregnant women, while the stimulated cytokine expression was higher in the PE group than in the other two groups studied. Stimulation of monocytes from preeclamptic and non-pregnant women with MSU induced increased ...